Plato and the power of images - Edmonds, Radcliffe G., III, 1970- (Mnemosyne, Supplements, 2017)
Plato is well known both for the harsh condemnations of images and image-making poets that appear in his dialogues and for the vivid and intense imagery that he himself uses in his matchless prose. Through their resemblance to true reality, images have the power to move their viewers to action and to change themselves, but because of their distance from true reality, that power always remains problematic. Two recurrent problems addressed here are how an image resembles what it represents and how to avoid mistaking that image for what it represents. Plato and the Power of Images comprises twelve chapters on the ways Plato has used images, and the ways we could, or should, understand their status as images.